The innovation chain in rail transport - Wojciech Dinges; Jana Pieriegud (ACTA INNOVATIONS, 2016)
The paper proposes a classification of innovations in rail transport by compiling a catalog of innovations and introduces the notions of innovation diffusion and innovation chain. It also provides examples of innovative products and technology solutions developed by Polish manufacturers.